Flame-retardant gel electrolyte based on in-situ polymerization, preparation method and application

By using aluminum hydroxide and a metal organic frame double-layered ammonium polyphosphate as a flame retardant additive in the gel electrolyte, the problems of high flammability in the gel electrolyte and the electrochemical performance after the addition of the flame retardant are solved, and the problem of high flammability in the gel electrolyte is achieved. Flame-retardant gel electrolyte with high ionic conductivity, good thermal stability and excellent electrochemical properties.

CN119463068APending Publication Date: 2025-02-18龙子湖新能源实验室 +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411633995.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The combustible electrolyte content in existing gel electrolytes is high, and there is a risk of thermal runaway. Commonly used flame retardants such as triphenyl phosphate and ammonium polyphosphate will reduce ionic conductivity and electrochemical properties when added too much.

Method used

Aluminum polyphosphate double-layer coated with aluminum hydroxide and metal organic frame (MOF) is used as a flame retardant additive to polymerize in situ in the electrolyte to form a flame retardant gel electrolyte. Improves flame retardant efficiency through aluminum hydroxide coating, and MOF shells optimize ion transport and electrochemical properties.

Benefits of technology

The ionic conductivity, thermal stability and electrochemical stability of gel electrolyte are improved, and the discharge specific capacity, cycling performance and safety performance of lithium batteries are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463068A_ABST
    Figure CN119463068A_ABST
Patent Text Reader

Abstract

The invention provides a flame-retardant gel electrolyte based on in-situ polymerization as well as a preparation method and application of the flame-retardant gel electrolyte. The preparation method comprises the following steps: adding a monomer, a cross-linking agent, a double-layer coated flame-retardant additive and an initiator into an electrolyte, fully and uniformly stirring to form an electrolyte precursor, and carrying out thermal initiation in-situ polymerization on the precursor to obtain the flame-retardant gel electrolyte. The electrolyte provided by the invention has the characteristics of high ionic conductivity, good thermal stability and good electrochemical stability. The high-safety flame-retardant lithium battery prepared based on the flame-retardant composite electrolyte shows excellent specific discharge capacity, good cycle performance and high safety performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of gel electrolytes, and in particular relates to a flame retardant gel electrolyte based on in-situ polymerization, a preparation method and an application thereof. Background Art

[0002] With the rapid development of new energy vehicles, more stringent requirements are placed on the energy density, safety and stability of batteries. Solid-state batteries are expected to be used in electric vehicles, consumer electronic devices and other fields as the next generation of high-performance electrochemical energy storage devices because they take into account both energy density and safety performance. However, solid-state batteries are difficult to develop and have high process requirements, and mass production cannot be achieved immediately. As an intermediate state between liquid electrolytes and solid electrolytes, gel electrolytes have excellent ionic conductivity and low interface resistance, and are a more promising choice for high-performance lithium-ion batteries. However, the content of flammable electrolyte in gel electrolytes is high, and after being ignited, highly flammable electrolyte vapor is formed, and there is still a large risk of thermal runaway. At the same time, common polymer matrices such as polymethyl methacrylate (PMMA) and polyethylene oxide (PEO) are also highly flammable, which poses serious safety hazards to quasi-solid-state batteries.

[0003] Adding flame retardants to batteries is one of the effective measures commonly used to ensure the safety of batteries and is relatively economical and practical. Chinese invention patent CN114400373 A uses phosphate flame retardant solvents, polyvinylidene fluoride and / or vinyl fluoride polymers, and ion conductor active metal salts as raw materials to prepare flame retardant gel electrolytes by impregnation method, and prepares gel electrolytes with good flame retardant effects. However, phosphonate flame retardant solvents themselves have low flame retardant efficiency and are incompatible with graphite and metal lithium negative electrodes. It is difficult to form a stable SEI on the negative electrode surface, resulting in battery cycle failure.

[0004] Chinese invention patent CN108878969A The present invention uses electrospinning to prepare a lithium ion battery polymer membrane of triphenyl phosphate / poly(vinylidene fluoride-hexafluoropropylene) / poly(butyl methacrylate-acrylonitrile-styrene). The flame retardant gel electrolyte has improved the flame retardancy to a certain extent while ensuring the stability of the original gel electrolyte. However, the flame retardant efficiency of triphenyl phosphate itself is not high, and adding too much will reduce the ionic conductivity and significantly reduce the electrochemical performance of the battery.

[0005] Ammonium polyphosphate (APP) is a low-cost and most widely used flame retardant additive. APP expands when heated, and decomposes non-volatile phosphorus oxides and polyphosphoric acid to cover the surface of the electrode material, isolate oxygen and achieve the purpose of flame retardancy. At the same time, APP decomposes under heat to release gases such as nitrogen and ammonia. These gases are not easy to burn and dilute the oxygen in the air, thereby blocking the supply of oxygen. However, the flame retardant effect of APP itself is insufficient. Adding a large amount of APP to the battery will reduce the ionic conductivity and significantly reduce the electrochemical performance of the battery. Chinese invention patent CN115693016B uses aluminum hydroxide to coat the surface of ammonium polyphosphate (APP) and apply it to the lithium-ion battery separator. This method improves the flame retardancy of APP and can significantly improve the problem of poor heat resistance and flame retardancy of the existing separator. However, this method cannot solve the problem of low ionic conductivity caused by adding APP to the polymer electrolyte. Summary of the invention

[0006] In view of the above problems existing in the prior art, the present invention provides a flame-retardant gel electrolyte based on in-situ polymerization, a preparation method and an application thereof: a flame-retardant gel electrolyte is formed by in-situ polymerization of a flame-retardant additive and a polymer monomer in an electrolyte having a double-layer coating structure of aluminum oxide (ATH) and a metal organic framework (MOF); ATH is coated to form a synergistic effect between ATH and APP to improve the flame retardant efficiency of the flame retardant; ATH is used to form a protective layer to prevent APP from participating in the side reactions inside the battery; MOF shell layer is used for secondary coating to further protect APP from the influence of side reactions; and the special structure of MOF is used to optimize the efficiency of ion transmission and deposition behavior to improve the ionic conductivity of the electrolyte.

[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions: In a first aspect, the present invention provides a flame retardant gel electrolyte, wherein the preparation method thereof comprises the following steps: (1) Preparation of double-layer coated flame retardant additives: a. Preparation of aluminum hydroxide coated ammonium polyphosphate (ATH-APP): Disperse ammonium polyphosphate (APP) and surfactant in anhydrous ethanol, gradually add aluminum chloride solution and stir well, adjust the pH to 7.5 with sodium bicarbonate or monohydrate ammonia solution and stir to react, centrifuge, wash and dry after the reaction to obtain aluminum hydroxide coated ammonium polyphosphate (ATH-APP); b. Preparation of double-layer coated flame retardant additive: adding aluminum hydroxide coated ammonium polyphosphate (ATH-APP) into methanol, stirring and dispersing it evenly, adding metal salt solution dissolved in methanol solution, stirring and dispersing it evenly again, and then quickly adding 2-methylimidazole dissolved in methanol, stirring vigorously and then aging it. After the aging reaction is completed, the obtained product is centrifuged, washed, and dried to obtain aluminum hydroxide and metal organic framework (MOF) double-layer coated ammonium polyphosphate flame retardant (MOF-ATH-APP); (2) Preparation of electrolyte precursor: adding monomer, cross-linking agent, double-layer coated flame retardant additive and initiator to the electrolyte, stirring well to obtain electrolyte precursor; (3) Preparation of flame-retardant gel electrolyte: The electrolyte precursor prepared in step (2) is heated in a closed environment to initiate in-situ polymerization to obtain a flame-retardant gel electrolyte.

[0008] Furthermore, the surfactant in step (1)a is one or more of polyethylene glycol tert-octylphenyl ether, polyvinyl pyrrolidone (PVP), and polyoxyethylene lauryl ether; the metal salt in step (1)b is one or both of zinc salt and cobalt salt, the mass fraction of the surfactant in the ammonium polyphosphate is 0.5% to 2%, the mass fraction of aluminum chloride in the ammonium polyphosphate is 5% to 50%, and the degree of polymerization of the ammonium polyphosphate is ≥1000.

[0009] Furthermore, the stirring reaction time in step (1) a is 2-4 h.

[0010] Furthermore, in step (1) b, the mass ratio of the metal salt to ATH-APP is (0.5-2):1, and the mass ratio of 2-methylimidazole to the metal salt is (1-1.2):1.

[0011] Furthermore, in step (1) b, after vigorous stirring for 5-30 min, the mixture is allowed to stand for 8-24 h to complete the reaction.

[0012] Furthermore, in step (2), the mass fraction of the cross-linking agent in the monomer is 0.5% to 30%, the mass fraction of the double-layer coated flame retardant additive in the monomer and the cross-linking agent is 0.5% to 10%, the mass fraction of the initiator in the monomer and the cross-linking agent is 0.1% to 5%, and the mass fraction of the monomer and the cross-linking agent in the electrolyte is 3% to 30%.

[0013] Furthermore, the monomer described in step (2) is one or more of methyl methacrylate, butyl acrylate, and trifluoroethyl acrylate; the cross-linking agent described in step (2) is one or two of triethylene glycol dimethacrylate, pentaerythritol tetraacrylate, and polyethylene glycol diacrylate; the initiator described in step (2) is one or more of azobisisobutyronitrile, dimethyl azobisisobutyrate, and azobisisoheptylnitrile; the electrolyte described in step (2) is a lithium salt electrolyte, and the lithium salt electrolyte is a lithium hexafluorophosphate electrolyte or a bistrifluoromethanesulfonyl imide lithium electrolyte.

[0014] Furthermore, the heating initiation temperature in step (3) is 25-80° C. and the heating time is 6-48 hours.

[0015] The invention also provides a flame retardant gel electrolyte based on an in-situ polymer prepared by the preparation method.

[0016] In a second aspect, the present invention provides a high-safety lithium battery using the flame-retardant gel electrolyte described in the first aspect.

[0017] Preferably, the lithium-ion battery uses lithium iron phosphate, lithium nickel cobalt manganese oxide or lithium cobalt oxide as the positive electrode, lithium sheet or graphite as the negative electrode, and the flame-retardant gel electrolyte as the electrolyte.

[0018] Furthermore, the electrolyte precursor group containing the double-layer coated flame retardant additive is injected into a lithium battery, and the heating is used to initiate polymerization to form a flame retardant gel lithium battery with high safety performance.

[0019] Compared with the prior art, the present invention has at least the following beneficial effects: 1. The present invention firstly prepares ATH-APP by coating a layer of aluminum hydroxide (ATH) on the surface of core APP by coprecipitation method, and then in situ grows MOF shell on the surface of ATH-APP, successfully preparing an ammonium polyphosphate (APP) flame retardant material with a metal organic framework (MOF) and aluminum hydroxide double-layer coating structure, and further preparing it into a flame retardant gel electrolyte. Through ATH coating, ATH and APP form a synergistic effect, improving the flame retardant efficiency of the flame retardant, and using ATH to form a protective layer to prevent APP from participating in the internal side reactions of the battery. Through the secondary coating of MOF shell, APP is further protected from the influence of side reactions. In addition, the special structure of MOF is used to optimize the efficiency and deposition behavior of ion transmission, and the ionic conductivity of the electrolyte is improved.

[0020] 2. Due to the above reasons, the flame-retardant gel electrolyte of the present invention has high ionic conductivity, good thermal stability and electrochemical stability.

[0021] 3. Due to the above reasons, the lithium battery prepared with the flame-retardant gel electrolyte of the present invention exhibits higher discharge specific capacity, better cycle performance and higher safety performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a comparison diagram of a gel electrolyte before gelling (a) and after gelling (b) according to Example 1 of the present invention; Figure 2 This is a photo of voltage testing after acupuncture testing in Example 1 of the present invention. DETAILED DESCRIPTION

[0023] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementations. It should be understood by those skilled in the art that the specific implementations are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0024] Example 1 The flame retardant gel electrolyte preparation method of this embodiment is as follows: (1) Preparation of double-layer coated flame retardant additives: a. Preparation of aluminum hydroxide-coated ammonium polyphosphate (ATH-APP): 15g APP and 0.1g polyethylene glycol tert-octylphenyl ether were dispersed in 100mL anhydrous ethanol. At the same time, 5g aluminum chloride was dissolved in 25mL deionized water to prepare aluminum chloride solution. The aluminum chloride solution was gradually added to the above ethanol solution and stirred thoroughly. The pH was adjusted to 7.5 with 10% sodium bicarbonate solution, and the mixture was stirred for 2h. After the reaction was completed, the product was centrifuged, washed, and dried to obtain ATH-APP. b. Preparation of double-layered flame retardant additive: 10g of ATH-APP prepared above was added to methanol and stirred thoroughly to disperse evenly, then 15g of Zn(NO3)2·6H2O dissolved in methanol was added, stirred at room temperature for 3 h, then 16g of 2-methylimidazole dissolved in methanol was quickly added to the bottle, stirred vigorously at room temperature for 5 min, and aged for 12 h to complete the reaction. After the reaction was completed, the product was centrifuged, washed, and dried to obtain an ammonium polyphosphate flame retardant (MOF-ATH-APP) double-layered with aluminum hydroxide and metal organic framework (MOF).

[0025] (2) Preparation of electrolyte precursor: 1.8 g polymethyl methacrylate, 0.2 g triethylene glycol dimethacrylate, 0.1 g MOF-ATH-APP and 0.06 g initiator were added to 18 g electrolyte (1 mol / L LIPF6, EC:DMC:EMC=1:1:1), and stirred thoroughly to obtain an electrolyte precursor.

[0026] (3) Preparation of flame-retardant gel electrolyte: The precursor prepared in step (2) was heated at 45° C. for 12 h in a closed environment to initiate in-situ polymerization to obtain a flame-retardant gel polymer electrolyte.

[0027] Assembly of stainless steel symmetric cell: 45 μL of gel electrolyte precursor was dripped onto the PP separator to assemble a stainless steel / PP (including precursor) / stainless steel symmetric cell. The sealed cell was placed in a 45°C oven and heated for 12 hours. The precursor solution was in situ polymerized under thermal initiation conditions to form a gel electrolyte. Its impedance was tested by an electrochemical workstation, and its ionic conductivity was calculated by the formula δ = L / (RS) (δ is the ionic conductivity of the electrolyte membrane, L is the thickness of the electrolyte membrane, R is the grain boundary impedance of the electrolyte, and S is the actual contact area between the electrolyte membrane and the steel sheet).

[0028] Assembly of stainless steel to lithium battery: 45 μL of gel electrolyte precursor was dripped onto the PP separator to assemble a stainless steel / PP (including precursor) / lithium symmetrical battery. The sealed battery was placed in a 45°C oven and heated for 12 hours. The precursor solution was polymerized in situ under thermal initiation conditions to form a gel electrolyte, and its electrochemical window was tested by an electrochemical workstation.

[0029] The preparation method of the solid-state lithium battery using the gel electrolyte prepared above is as follows: (1) Preparation of positive electrode LiNi 0.8 Co 0.1 Mn 0.1 O2 is used as the positive electrode active material, Super-P is used as the conductive agent, and polyvinylidene fluoride (PVDF) is used as the binder. 0.8 Co 0.1 Mn 0.1 The positive electrode slurry is prepared with a mass ratio of O2, Super-P and PVDF of 94:3:3; the positive electrode slurry is evenly coated on both sides of the positive electrode current collector aluminum foil, dried at room temperature, transferred to an oven for further drying, and then cold pressed and cut to obtain the positive electrode sheets. (2) Preparation of graphite negative electrode Using graphite as the negative electrode active material, Super-P as the conductive agent, sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) as the binder, the negative electrode slurry was prepared according to the mass ratio of graphite, Super-P, CMC and SBR of 95:1:1.5:2.5; the negative electrode slurry was evenly coated on the two surfaces of the negative electrode current collector copper foil, dried at room temperature and then transferred to an oven for further drying, and then cold pressed and cut to obtain the negative electrode sheet. (3) Preparation of flame-retardant gel lithium battery The positive electrode sheet, PP separator and negative electrode sheet prepared by the above preparation method are stacked in a zigzag manner to assemble into a soft-package battery, into which the gel electrolyte precursor prepared by the above preparation method is injected with an injection coefficient of 2.5g / Ah. After the injection and sealing, the battery is allowed to stand at 45°C for 12h, and then evaporated to obtain a flame-retardant gel lithium battery.

[0030] Example 2 The other conditions were the same as those in Example 1, except that the mass of aluminum chloride added during the preparation of the double-layer coated flame retardant additive in step (1) was 0.75 g.

[0031] Example 3 The other conditions were the same as those in Example 1, except that the mass of aluminum chloride added during the preparation of the double-layer coated flame retardant additive in step (1) was 7.5 g.

[0032] Example 4 The other conditions were the same as those in Example 1, except that in the preparation of the double-layer coated flame retardant additive in step (1), the added mass of Zn(NO3)2·6H2O was 5 g, and the added mass of 2-methylimidazole was 5.5 g.

[0033] The other conditions of Example 5 are the same as those of Example 1, except that in the preparation process of the double-layer coated flame retardant additive in step (1), the added mass of Zn(NO3)2·6H2O is 20 g, and the added mass of 2-methylimidazole is 21 g.

[0034] Example 6 The other conditions are the same as those in Example 1, except that in the preparation process of the double-layer coated flame retardant additive in step (1), Zn(NO3)2·6H2O is replaced by Co(NO3)2·6H2O.

[0035] Example 7 The other conditions were the same as those in Example 1, except that in step (2), the amount of MOF-ATH-APP in the preparation of the electrolyte precursor was 0.01 g.

[0036] Example 8 The other conditions were the same as those in Example 1, except that in step (2), the amount of MOF-ATH-APP in the preparation of the electrolyte precursor was 0.2 g.

[0037] Comparative Example 1 The other conditions are the same as those in Example 1, except that the flame retardant APP added to the electrolyte precursor is not coated. The specific method for preparing the flame retardant gel electrolyte is as follows: (1) Preparation of electrolyte precursor: Add 1.8 g polymethyl methacrylate, 0.2 g triethylene glycol dimethacrylate, 0.1 g APP and initiator to 18 g electrolyte (1 mol / L LIPF6 EC:DMC:EMC=1:1:1), stir well to obtain electrolyte precursor.

[0038] (2) Preparation of flame-retardant gel electrolyte: The precursor prepared in step (1) was heated at 45° C. for 12 h in a closed environment to initiate in-situ polymerization to obtain a flame-retardant gel polymer electrolyte.

[0039] Comparative Example 2 The other conditions are the same as those in Example 1, except that the flame retardant APP added to the electrolyte precursor is only coated with aluminum hydroxide. The method for preparing the flame retardant gel electrolyte is as follows: (1) Preparation of aluminum hydroxide-coated ammonium polyphosphate (ATH-APP): 15 g APP and 0.1 g polyethylene glycol tert-octylphenyl ether were dispersed in 100 mL of anhydrous ethanol. At the same time, 5 g aluminum chloride was dissolved in 25 mL of deionized water to prepare an aluminum chloride solution. The aluminum chloride solution was gradually added to the above ethanol solution and stirred thoroughly. The pH was adjusted to 7.5 with 10% sodium bicarbonate and the reaction was stirred for 2 h. After the reaction was completed, the product was centrifuged, washed, and dried to obtain ATH-APP. (2) Preparation of electrolyte precursor: Add 1.8 g polymethyl methacrylate, 0.2 g triethylene glycol dimethacrylate, 0.1 g ATH-APP and initiator to 18 g electrolyte (1 mol / L LIPF6 EC:DMC:EMC=1:1:1), stir well to obtain electrolyte precursor.

[0040] (3) Preparation of flame-retardant gel electrolyte: The precursor prepared in step (2) was heated at 45° C. for 12 h in a closed environment to initiate in-situ polymerization to obtain a flame-retardant gel polymer electrolyte.

[0041] Comparative Example 3 The other conditions are the same as those in Example 1, except that the flame retardant APP added to the electrolyte precursor is only subjected to MOF coating treatment. The method for preparing the flame retardant gel electrolyte is as follows: (1) Preparation of MOF-coated ammonium polyphosphate (ATH-APP): 10 g APP was added to methanol and stirred thoroughly to disperse evenly. Then 15 g Zn(NO3)2·6H2O dissolved in methanol was added to the bottle and stirred at room temperature for 3 h. Then 16 g 2-methylimidazole dissolved in methanol was quickly added to the bottle and stirred vigorously at room temperature for 5 min. The mixture was aged for 12 h to complete the reaction. After the reaction was completed, the product was centrifuged, washed, and dried to obtain a metal organic framework (MOF)-coated ammonium polyphosphate flame retardant (MOF-APP).

[0042] (2) Preparation of electrolyte precursor: Add 1.8 g polymethyl methacrylate, 0.2 g triethylene glycol dimethacrylate, 0.1 g MOF-APP and initiator to 18 g electrolyte (1 mol / L LIPF6 EC:DMC:EMC=1:1:1), stir well to obtain electrolyte precursor.

[0043] (3) Preparation of flame-retardant gel electrolyte: The precursor prepared in step (2) was heated at 45° C. for 12 h in a closed environment to initiate in-situ polymerization to obtain a flame-retardant gel polymer electrolyte.

[0044] Comparative Example 4 The other conditions are the same as those in Example 1, except that the flame retardant APP added to the electrolyte precursor is first coated with MOF and then with aluminum hydroxide. The method for preparing the flame retardant gel electrolyte is as follows: (1) Preparation of double-layer reverse-coated flame retardant additives: a. Preparation of MOF-coated ammonium polyphosphate (MOF-APP): 10g APP was added to methanol and stirred thoroughly to disperse evenly, then 15g Zn(NO3)2·6H2O dissolved in methanol was added to the bottle, stirred at room temperature for 3 h, then 16g 2-methylimidazole dissolved in methanol was quickly added to the bottle, stirred vigorously at room temperature for 5 min, and aged for 12 h to complete the reaction. After the reaction was completed, the product was centrifuged, washed, and dried to obtain a metal organic framework (MOF)-coated ammonium polyphosphate flame retardant (MOF-APP).

[0045] b. Preparation of double-layer reverse-coated flame retardant additive (ATH-MOF-APP): 15g MOF-APP and 0.1g polyethylene glycol tert-octylphenyl ether were dispersed in 100mL anhydrous ethanol. At the same time, 5g aluminum chloride was dissolved in 25mL deionized water to prepare aluminum chloride solution. The aluminum chloride solution was gradually added to the above ethanol solution and fully stirred. The pH was adjusted to 7.5 with 10% sodium bicarbonate and stirred for 2h. After the reaction was completed, the product was centrifuged, washed, and dried to obtain MOF-ATH-APP; (1) Preparation of electrolyte precursor: Add 1.8 g polymethyl methacrylate, 0.2 g triethylene glycol dimethacrylate, 0.1 g MOF-ATH-APP and initiator to 18 g electrolyte (1 mol / L LIPF6 EC:DMC:EMC=1:1:1), stir well to obtain electrolyte precursor.

[0046] (2) Preparation of flame-retardant gel electrolyte: The precursor prepared in step (2) is heated at 45° C. for 12 h in a closed environment to initiate in-situ polymerization to obtain a flame-retardant gel polymer electrolyte.

[0047] Comparative Example 5 The other conditions are the same as those in Example 1, except that the flame retardant additive APP is not added. The preparation method of the gel electrolyte is as follows: (1) Preparation of electrolyte precursor: Add 1.8 g polymethyl methacrylate, 0.2 g triethylene glycol dimethacrylate and initiator to 18 g electrolyte (1 mol / L LIPF6 EC:DMC:EMC=1:1:1), stir well to obtain electrolyte precursor.

[0048] (2) Preparation of flame-retardant gel electrolyte: The precursor prepared in step (2) is heated at 45° C. for 12 h in a closed environment to initiate in-situ polymerization to obtain a flame-retardant gel polymer electrolyte.

[0049] The solid electrolytes and lithium metal batteries of Examples 1-8 and Comparative Examples 1-5 were tested according to the items in Tables 1 and 2. The ionic conductivity and voltage window were tested by impedance testing using an electrochemical workstation, the specific capacity, initial efficiency and cycle life were tested using a Xinwei charge and discharge instrument, and the puncture test was performed using a puncture test machine.

[0050] Table 1 Performance test results of embodiments and comparative examples

[0051] Table 2 Performance test results of embodiments and comparative examples

[0052] According to the data in Table 1 and Table 2, the flame-retardant gel electrolyte prepared by the in-situ polymerization technology of the present invention exhibits high ionic conductivity, wide voltage window and excellent cycle performance. In addition, the gel electrolyte exhibits high safety stability without fire or explosion in the needle puncture test. Compared with Examples 1-8, the gel electrolyte in Comparative Example 5 does not add a flame retardant, while the present invention adds a polyphosphate flame retardant (MOF-ATH-APP) containing a double-layer coating structure. The results show that the gel electrolyte of the present invention adding MOF-ATH-APP has significant improvements in ionic conductivity, electrochemical window, gram capacity, cycle performance and safety performance. Compared with the results of Examples 1-8 and Comparative Example 1, the gel electrolyte containing MOF-ATH-APP of the present invention has significantly improved ionic conductivity, electrochemical window, gram capacity, cycle performance and safety performance compared with the gel electrolyte containing uncoated polyphosphate flame retardant (APP). Compared with the results of Examples 1-8 and Comparative Example 2, the gel electrolyte containing MOF-ATH-APP of the present invention has significantly improved ionic conductivity, electrochemical window, gram capacity, cycle performance and safety performance compared with the gel electrolyte with only lithium hydroxide coated flame retardant additive (ATH-APP), indicating that the outer layer of the MOF coating of the present invention can improve the electrolysis The results of Example 1-8 are compared with those of Comparative Example 3. The ionic conductivity, electrochemical window, specific capacity, and cycle performance of the gel electrolyte containing MOF-ATH-APP in the present invention are basically similar to those of the gel electrolyte with only metal organic framework material coated flame retardant additive (MOF-APP), but the safety performance is significantly improved, indicating that ATH and APP form a synergistic effect to improve the safety performance of the battery; The results of Example 1-8 are compared with those of Comparative Example 4. The ionic conductivity, electrochemical window, specific capacity, cycle performance and safety performance of the gel electrolyte containing MOF-ATH-APP in the present invention are significantly improved compared to the gel electrolyte containing reverse coated flame retardant additive (MOF-APP), indicating that ATH forms a synergistic effect with APP in the inner layer to improve the flame retardant efficiency of the flame retardant, and MOF optimizes the efficiency and deposition behavior of ion transmission in the outer layer to improve the ionic conductivity of the electrolyte. This structure is more conducive to the simultaneous improvement of electrolyte electrochemistry and safety performance.

[0053] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing a flame retardant gel electrolyte based on in-situ polymer, characterized in that It includes the following steps: (1) Preparation of double-layer coated flame retardant additives: a. Preparation of aluminum hydroxide coated ammonium polyphosphate (ATH-APP): Disperse ammonium polyphosphate (APP) and surfactant in anhydrous ethanol, gradually add aluminum chloride solution and stir well, adjust the pH to 7.5 with sodium bicarbonate or monohydrate ammonia solution and stir to react, centrifuge, wash and dry after the reaction to obtain aluminum hydroxide coated ammonium polyphosphate (ATH-APP); b. Preparation of double-layer coated flame retardant additive (MOF-ATH-APP): add aluminum hydroxide coated ammonium polyphosphate (ATH-APP) into methanol, stir and disperse it evenly, add metal salt solution dissolved in methanol solution, stir and disperse it evenly again, then quickly add 2-methylimidazole dissolved in methanol, stir vigorously and then age it statically, after the aging reaction is completed, the obtained product is centrifuged, washed and dried to obtain aluminum hydroxide and metal organic framework (MOF) double-layer coated ammonium polyphosphate flame retardant (MOF-ATH-APP); (2) Preparation of electrolyte precursor: adding monomer, cross-linking agent, double-layer coated flame retardant additive and initiator to the electrolyte, stirring well to obtain electrolyte precursor; (3) Preparation of flame-retardant gel electrolyte: The electrolyte precursor prepared in step (2) is heated in a closed environment to initiate in-situ polymerization to obtain a flame-retardant gel electrolyte.

2. The method for preparing a flame retardant gel electrolyte according to claim 1, characterized in that: The surfactant in step (1)a is one or more of polyethylene glycol tert-octylphenyl ether, polyvinyl pyrrolidone (PVP), and polyoxyethylene lauryl ether; the metal salt in step (1)b is one or both of zinc salt and cobalt salt, the mass fraction of the surfactant in the ammonium polyphosphate is 0.5% to 2%, the mass fraction of aluminum chloride in the ammonium polyphosphate is 5% to 50%, and the degree of polymerization of the ammonium polyphosphate is ≥1000.

3. The method for preparing a flame retardant gel electrolyte according to claim 1, characterized in that: The stirring reaction time in step (1) a is 2-4 h.

4. The method for preparing a flame retardant gel electrolyte according to claim 1, characterized in that: In step (1) b, the mass ratio of the metal salt to ATH-APP is (0.5-2):1, and the mass ratio of 2-methylimidazole to the metal salt is (1-1.2):

1.

5. The method for preparing a flame retardant gel electrolyte according to claim 1, characterized in that: In step (1) b, after vigorous stirring for 5-30 min, the mixture is allowed to stand for 8-24 h to complete the reaction.

6. The method for preparing a flame retardant gel electrolyte according to claim 1, characterized in that: In step (2), the mass fraction of the cross-linking agent in the monomer is 0.5% to 30%, the mass fraction of the double-layer coated flame retardant additive in the monomer and the cross-linking agent is 0.5% to 10%, the mass fraction of the initiator in the monomer and the cross-linking agent is 0.1% to 5%, and the mass fraction of the monomer and the cross-linking agent in the electrolyte is 3% to 30%.

7. The method for preparing a flame retardant gel electrolyte according to claim 1, characterized in that: The monomer described in step (2) is one or more of methyl methacrylate, butyl acrylate, and trifluoroethyl acrylate; the cross-linking agent described in step (2) is one or two of triethylene glycol dimethacrylate, pentaerythritol tetraacrylate, and polyethylene glycol diacrylate; the initiator described in step (2) is one or more of azobisisobutyronitrile, dimethyl azobisisobutyrate, and azobisisoheptylnitrile; the electrolyte described in step (2) is a lithium salt electrolyte, and the lithium salt electrolyte is a lithium hexafluorophosphate electrolyte or a bistrifluoromethanesulfonyl imide lithium electrolyte.

8. The method for preparing a flame retardant gel electrolyte according to claim 1, characterized in that: The heating initiation temperature of step (3) is 25-80° C. and the heating time is 6-48 hours.

9. An in-situ polymer-based flame retardant gel electrolyte prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the flame-retardant gel electrolyte based on in-situ polymer according to claim 9 in a lithium battery.

Citation Information

Patent Citations

  • Flame-retardant gel polymer electrolyte and preparation and application thereof

    CN108878969A

  • Flame-retardant gel electrolyte as well as preparation method and application thereof

    CN114400373A

  • A method for preparing heat-resistant and flame-retardant dual-functional composite fiber membrane

    CN115693016B